Composing a further life : the age of active wisdom - Bateson, Mary Catherine (Alfred A. Knopf, 2010)
Mary Catherine Bateson sees aging today as an "improvisational art form calling for imagination and willingness to learn," and in this ardent, affirming study, she relates the experiences of men and women---herself included---who, upon entering this second adulthood, have found new meaning and new ways to contribute, composing their lives in new patterns.